Análise das práticas administrativas de uma fundação empresarial aberta - Pinto, Wagner de Siqueira (2001)
The goal of this work is to present a contribution to the critical analysis of the rationality that supports the action of the members of productive organizations, starting from a perspective of the man's emancipation in the ambit of the work. The focus of attention is related to the administrative practices of one of the largest Brazilian's private foundations that they were analyzed based on the distinction among instrumental and substantive rationality and of the theory of the communicative action. The main research method used was the 'participant observation' that allowed to the author to verify in loco the rationality that permeates the administrative practices of the researched Foundation. The importance of this study is in the fact that are scarce the studies about the management of nonprofit organizations. For increasing, every day, the emphasis that the society is giving to the third sector, for the expectation of its growth, so much in quantitative level as of influence degree about the people's life, and for placing in the position of offering answers and solutions for the problems that the State doesn't get to solve, the third sector and its organizations need a theoretical reference for its administration that is coherent with its emancipatory purpose. The results led to conclusions that alert the managers of the private foundations to review the practices adopted in the management of those organizations and stimulate the debate and the continuity of researches on the theme.